CHEMICAL COMPOSITIONS OF CRAB NEBULA FILAMENTS - Holovatyy, V. V.; Melekh, B. Ya.; Havrylova, N. V. (Одеські астрономічні публікації, 2013)
The chemical compositions in filaments of Crab Nebula are obtained using two methods: new Ionization Correction Factors taking in to account density in homogeneities f the nebular gas, and new 3-stages method based on the optimized photoionization modeling of the nebular gas.